PERILAKU AGRESIF ANGGOTA ORGANISASI EMASYARAKATAN (ORMAS) âXâ DI PROVINSI D.I. YOGYAKARTA - Sutowo, Ibnu; Wibisono, Susilo (HUMANITAS (Jurnal Psikologi Indonesia), 2013)
AbstractThis research is aimed to understand psychological dynamics ofaggressive behaviors among the social organizationâs membersinJogjakarta. This research usedqualitative approach. Respondents were the active members of the social organization (ormas) âXâ in Jogjakarta. The result shows some factors that influence the aggressive behavior among the members, which are group influence, deindividuation, frustration, drug or alcoholic and physical environmental. The aggressive behaviors were done by the members of ormas âXâare included physical and verbalaggression. Physical aggressionswere done by member of ormas âXâsuch as destruction of public facilities, injuring another person and inter-group conflict. Verbal aggressionswere done by member of ormas âXâsuch as harassment, oppression and intimidation to the victims. The aggressive behaviors among the member of ormas X were done spontaneously. On the other hand, aggression done by ormas âXâ to other organization or group also includes an invisibility aggression such as refusing to supportother organization, rejection from agreement, and boycott the otherâs activities.Keywords: aggressive behavior, social organization (ormas).